Original paperEpidemiological aspects of pregnant women with human immunodeficiency virus in Brazil - Galăo, Eloísa A; Godoy, José Maria Pereira de; Bagarelli, Lúcia Buchalla; Perea, Lúcia Sílvia Aparecida; Oliani, Antonio Helio (Archives of Medical Science, 2007)
Introduction: The aims of the current study are to report on preliminary epidemiological data of pregnant women with human immunodeficiency virus (HIV). Material and methods: HIV tests of 4653 pregnant women from Săo José do Rio Preto, Brazil between May 1995 and May 1997 were assessed, and the following epidemiological aspects were noted: age ethnic background, number of gestations, marital status, type of delivery, and the patients’ knowledge about the disease including: forms of transmission, diseases associated with positive cases, and the difficulties in and evolution of the approach to the disease in Brazil. Statistical analysis used percentages with means and standard deviation. Results: HIV tests were positive in 48 (1.03%) of the pregnant women. The mean age was 24.3±0.6 years. 35 (72.9%) of the individuals were married and 13 (27.1%) had been pregnant one to four times previously. 52.0% knew they were HIV positive and in 23 (48.0%), diagnoses was made during the consultations for this pregnancy. In 25 (52.0%) the form of transmission was unknown; events and gravid diseases occurred in 4 (31.2%) cases. In 38 (79.2%) cases delivery occurred before the 36th week of gestation, with delivery being vaginal in 38 (79.2%) cases, and there were puerperal complications in 8 (16.7%). Conclusions: The routine examination to test for HIV during pregnancy allows the identification of women who are unaware of infection by the virus and performance of medicinal prevention for these pregnant.